Pengendalian trips, Megalurothrips usitatus (Bagnall) pada tanaman kacang hijau (Vigna radiata): Pengaruh waktu tanam dan periode pengendalian - Sri Wahyuni Indiati; Marida Santi Yudha Ika Bayu (Perhimpunan Entomologi Indonesia, 2020)
Megalurothrips usitatus (Bagnall), is the main pest on mung bean causing crop failures, thus the objective of this study was to determine the proper mung bean planting time and timing of thrips control, with minimal risk of yield loss. This experiment was conducted at Muneng Research Station, Probolinggo, East Java during dry season of 2015. This research was conducted using a split-plot in completely randomized design with planting time as the whole plot and pest control time treatment as a sub-plot with 2 repetitions. There were six planting time as the whole plot: first planting 20 May 2015, second planting 30 May 2015; third planting 9 June 2015; fourth planting 19 June 2015; fifth planting 29 June 2015, and sixth planting 9 July 2015. While, the pest control time treatment was done with an active agent fipronil insecticide as a sub-plot which consists of 4 treatments: (1) without insecticide treatment during vegetative and generative phase, (2) insecticide application during generative phase only, (3) insecticide application during vegetative phase only, and (4) full insecticide treatment during vegetative and generative phase. The results showed that the symptom of thrips attack began to appear 21 days after planting (DAP) by observing initial curling of trifoliate leaves. The thrips population per plant increases with increasing plant age. The highest populations of thrips were found on the second planting time (end of May) combined with no control during vegetative and generative phase, which is 17.8 individuals/plant at 18 DAP. The highest yield lost, was found on first planting time (90.2%) and second planting time (85.6%), if there is no control during vegetative and generative phase. It is indicated that in May become the appropriate time as a critical period of mung bean against thrips attack. From this study it can be concluded that to reduce the risk of high yield losses due to thrips attacks is to avoid from planting green beans in May. In thrips endemic areas, pest control at the beginning of plant growth and during the vegetative phase is a determining factor for the yield of mung bean. The season of “bediding” can be a warning sign for farmers before thrips infestation and to immediately take pest control measures.